Evaluation of Plasmatic Procalcitonin in Healthy, and in Systemic Inflammatory Response Syndrome (SIRS) Negative or Positive Colic Horses - Irene Nocera; Francesca Bonelli; Valentina Vitale; Valentina Meucci; Giuseppe Conte; Eduard Jose-Cunilleras; Luis Alfonso Gracia-Calvo; Micaela Sgorbini (Animals, 2021)
Colic horses show systemic inflammatory response syndrome (SIRS) clinical signs. Procalcitonin (PCT) showed increased circulating levels in sick horses. This study compares plasma PCT concentrations in healthy vs. SIRS negative/positive colic horses over time, and evaluates PCT and SIRS score potential correlation, to verify the usefulness of PCT for the evaluation of SIRS severity. Ninety-one horses were included; 43/91 were healthy, on basis of physical examination, blood work and SIRS score (score = 0), while 48/91 were sick colic horses, classified as SIRS-negative (score < 2) and positive (score ≥ 2). Moreover, a 0–6 point-scale SIRS score was calculated (assessing mucous membrane color and blood lactate concentration). PCT was evaluated at admission, and at 24, 48, 72 and 96 h, using a commercial kit for equine species. We verified by the ANOVA test PCT differences between healthy vs. colic horses, healthy vs. SIRS-negative or SIRS-positive colic horses, at all sampling times, and the correlation between the SIRS score at admission with the SIRS score. Statistically significant differences were detected between healthy vs. all colic horses and between healthy vs. SIRS-positive or negative horses at all sampling times. No correlation was observed between the SIRS score at admission and PCT values. PCT was statistically higher in colic horses compared to the healthy ones, suggesting a role as a biomarker for colic.